Política comercial y mujer en la Alianza del Pacífico - López, Dorotea (2018)
The relation between trade and gender is complex, and has not been deeply analysed in the case of Latin American countries. Mainstream economics argue that trade is gender-neutral, but the discussion should focus whether trade policy could be oriented to foster women’s economic inclusion. It is well known that, with the adequate policies, women’s economic empowerment could positively impact economic growth and reduce poverty, and therefore, trade policy may become an instrument to achieve this objective. The Pacific Alliance, a novel integration scheme, has considered women economic inclusion into their work and objectives. In this article, we aim to review trade policies implemented at regional and domestic level amongst the four Pacific Alliance member countries: Colombia, Chile, Mexico and Peru. For this, the article is divided as follows. The first section reviews the literature on trade policy and gender issues, specifically in women inclusion aspects. The second section presents those policies discussed and implemented at the Pacific Alliance. The third section individually reviews member countries trade policies on women economic inclusion and empowerment. Finally, we present some conclusions and policy recommendations.